Sustaining Heritage in South-East Europe: Working with the Council of Europe, 2003–10. (April 2013) - Bold, John
Abstract : The paper outlines the principles, outcomes, and impacts of the Council of Europe's heritage-rehabilitation project in South-East Europe, the Integrated Rehabilitation Project Plan/Survey of the Architectural and Archaeological Heritage (IRPP/SAAH). It is suggested that, although the project began in 2003, before the adoption of the Faro Convention on the Value of Cultural Heritage for Society, it anticipated many of its themes, so in effect was putting theories into practice. The lessons learned from this continuing heritage project will contribute to future discussions on the theory and practice of heritage-led regeneration, in which the conservation of heritage is not an end in itself but a means to an end of social and economic development.